Roadmap for Designing Donor-<semantics>π</semantics>-Acceptor Fluorophores in UV-Vis and NIR Regions: Synthesis, Optical Properties and Applications - Guliz Ersoy; Maged Henary (Biomolecules)
Donor acceptor (D-<semantics>π</semantics>-A) fluorophores containing a donor unit and an acceptor moiety at each end connected by a conjugated linker gained attention in the last decade due to their conjugated system and ease of tunability. These features make them good candidates for various applications such as bioimaging, photovoltaic devices and nonlinear optical materials. Upon excitation of the D-<semantics>π</semantics>-A fluorophore, intramolecular charge transfer (ICT) occurs, and it polarizes the molecule resulting in the ‘push–pull’ system. The emission wavelengths of fluorophores can be altered from UV-vis to NIR region by modifying the donor unit, acceptor moiety and the <semantics>π</semantics> linker between them. The NIR emitting fluorophores with restricted molecular rotations are used in aggregation-induced emission (AIE). D-<semantics>π</semantics>-A fluorophores with carboxylic acid and cyano groups are preferred in photovoltaic applications, and fluorophores with large surface area are used for two photon absorbing applications. Herein, we report the synthesis, optical properties, and applications of various D-<semantics>π</semantics>-A fluorophores in UV-vis and NIR region.